Factors Contributing to the Success of Ultrasound‐Guided Native Renal Biopsy. (18th January 2016) - Kriegshauser, J. Scott; Patel, Maitray D.; Young, Scott W.; Chen, Frederick; Eversman, William G.; Chang, Yu-Hui H.; Smith, Maxwell
Abstract : Objectives: The purpose of this study was to evaluate factors contributing to the success of ultrasound‐guided native renal biopsy. Methods: We retrospectively identified patients who had ultrasound‐guided native renal biopsy at our institution over a 10‐year period. We reviewed the imaging and electronic medical records to collect demographic information and clinical data, including pathologic results. Biopsy samples were categorized and compared on the basis of the number of glomeruli (optimal [≥20] versus suboptimal [<20]) and the pathologist's reported diagnostic confidence (high confidence versus limited confidence). Procedure details, including the operator and the use of the cortical tangential approach, were also obtained. Results: For 282 patients with biopsies using 18‐gauge needles, the number of passes made was significantly higher for optimal ( P < .001) and high‐confidence ( P < .001) specimens than for suboptimal and limited‐confidence specimens. The cortical tangential approach was used more frequently for optimal ( P < .001) and high‐confidence ( P = .01) specimens than for suboptimal and limited‐confidence specimens. Radiologists routinely doing ultrasound‐guided procedures of all types had significantly more optimal ( P = .01) and high‐confidence ( P = .001) specimens than radiologists with limited ultrasound experience. The distance to the kidney, cortical thickness, glomerular filtration rate, and body mass index were not significant factors. Conclusions: The ultrasound‐guided procedural experience of the operator, taking more than 1 specimen, and the use of the cortical tangential approach significantly improved the pathologic material obtained during native renal biopsies.